2006
DOI: 10.1248/bpb.29.1618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dimethylsulfoxide on Metabolism and Toxicity of Acetaminophen in Mice

Abstract: Dimethylsulfoxide (DMSO) is frequently used as a solvent in various in vivo and in vitro experiments. The use of this solvent is favored especially when physicochemical properties of a test compound have not been well characterized such as in the case of natural products. But DMSO is not biologically inert. DMSO has numerous pharmacological effects, the most well-known of which is hydroxyl radical scavenging capacity. Therefore, it is suspected that toxicological implications of the interaction of DMSO with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…DMSO has been commonly used in biological studies as an inert solvent to dissolve drugs with low water solubility. However, DMSO has been known to attenuate liver injury induced by APAP overdose in rodents, and often the facts confound evaluation of the protective effects of compounds with poor water solubility against APAP-induced liver injury (47,48). In this study, we also confirmed that the treatment with 5% DMSO attenuated the increase in serum alanine aminotransferase levels and hepatocellular necrosis induced by APAP (400 mg/kg, i.p.)…”
Section: Discussionsupporting
confidence: 80%
“…DMSO has been commonly used in biological studies as an inert solvent to dissolve drugs with low water solubility. However, DMSO has been known to attenuate liver injury induced by APAP overdose in rodents, and often the facts confound evaluation of the protective effects of compounds with poor water solubility against APAP-induced liver injury (47,48). In this study, we also confirmed that the treatment with 5% DMSO attenuated the increase in serum alanine aminotransferase levels and hepatocellular necrosis induced by APAP (400 mg/kg, i.p.)…”
Section: Discussionsupporting
confidence: 80%
“…A study reported protection against APAP hepatotoxicity with a pan-caspase inhibitor in the absence of caspase activation (El-Hassan et al, 2003). However, the protection was caused by the solvent (dimethyl sulfoxide, DMSO) (Jaeschke et al, 2006), which is an effective inhibitor of P450 enzymes (Yoon et al, 2006). On the other hand, in cases of Fas- or TNF-induced hepatocellular apoptosis, caspase inhibitors are highly effective and completely eliminate cell death (Bajt et al, 2000; Jaeschke et al, 1998).…”
Section: Acetaminophen Hepatotoxicitymentioning
confidence: 99%
“…One of the most effective ways to prevent APAP toxicity is to interfere with the initial step of metabolic activation. Many solvents, such as dimethyl sulfoxide or ethanol, used to dissolve agents with limited water solubility effectively, compete with APAP for CYP metabolism even at very low doses (Jaeschke et al 2006; Park et al 1988; Sato and Lieber 1981; Yoon et al 2006). Extracts from plants and other sources contain numerous chemicals that can act as CYP inhibitors (Jiang et al 2015), but are rarely tested for this effect.…”
Section: Acetaminophen-based Modelmentioning
confidence: 99%